DIPATI UKUR DAN JEJAK PENINGGALANNYA DI KECAMATAN CIPARAY KABUPATEN BANDUNG (1627-1633) - Lasmiyati Lasmiyati (Patanjala: Journal of Historical and Cultural Research, 2016)
Figures are people who have the charisma and work. The work of a person can be a text or historical relics, either as a live or as petilasan (traces of something in the past eg. buildings, etc.). Dipati Ukur served the adipati (Duke) in Tatar Ukur and served as regent wedana of Priangan (1627-1733), suffered an unfortunate fate. He must bear removal as regent wedana and nomadic, following a dispute with Mataram Kingdom.  This study was conducted to answer the question who is Dipati Ukur?, has been active in what field?, and what legacy? The method used is the historical method which includes heuristics, criticism, interpretation, and historiography. The research results are to be obtained information that Dipati Ukur born in Purbolinggo Banyumas, Central Java. He was a descendant of Sunan Jambu Karang. From his wanderings after fighting a war against the Dutch in Batavia, he makes the building which is now a relic and petilasan (traces of something in the past eg. buildings, etc.). One proof of his legacy is the largest hill horn legacy in Sub-Ciparay, Bandung regency.